A compact model of the reverse gate-leakage current in GaN-based HEMTs. (December 2016) - Ma, Xiaoyu; Huang, Junkai; Fang, Jielin; Deng, Wanling
Highlights: Gate-leakage current of GaN-based HEMTs is modeled by possible mechanisms. The model accurately explains the gate-leakage phenomenon due to the traps. This model is straightforward and computationally-efficient. Abstract: The gate-leakage behavior in GaN-based high electron mobility transistors (HEMTs) is studied as a function of applied bias and temperature. A model to calculate this current is given, which shows that trap-assisted tunneling, trap-assisted Frenkel-Poole (FP) emission, and direct Fowler-Nordheim (FN) tunneling have their main contributions at different electric field regions. In addition, the proposed model clearly illustrates the effect of traps and their assistance to the gate leakage. We have demonstrated the validity of the model by comparisons between model simulation results and measured experimental data of HEMTs, and a good agreement is obtained.